APLIKASI FILE SHARING PEER TO PEER BERBASIS WEB MENGGUNAKAN WEBRTC WEB-BASED PEER TO PEER FILE SHARING APPLICATION USING WEBRTC - Andi Suprianto; Ivan Juan Kara (JURNAL REKAYASA INFORMASI, 2023)
One of the activities that are often carried out by computer users is file sharing. The absence of a standard on popular operating systems makes this activity not always easy to do if you want to send files to and from different operating systems. Installing third-party apps from the app store can also be inconvenient for novice users and inefficient if used only occasionally. The results of this study are web-based applications that can be used to carry out peer to peer file sharing activities using WebRTC technology and QR codes as an alternative signaling technique if the server is offline which was created using the Blazor framework and the C# programming language.Keywords : file sharing, peer to peer, WebRTC, QR code, Blazor